Off-design point modelling of a 420 MW CCGT power plant integrated with an amine-based post-combustion CO2 capture and compression process. (15th September 2016) - Adams, T.; Mac Dowell, N.
Highlights: Multi-scale modelling of CCGT with CO2 capture and compression. Evaluation of full- and part-load behaviour. Impact of exhaust gas recycle on process performance quantified. Financial evaluation performed for full- and part-load operation. Abstract: The use of natural gas for power generation is becoming increasingly important in many regions in the world. Given that the combined cycle gas turbine (CCGT) power stations are lower in capital cost and carbon intensity than their coal-fired counterparts, natural gas fired power stations are considered a vital part of the transition to a low carbon economy. However, CCGTs are not themselves "low carbon" and in order to reach a carbon intensity of less than 50 kg CO 2 /MWh, it will be necessary to decarbonise them via CCS, with post-combustion CCS currently regarded as being a promising technology for this application. In this study, we present a detailed model of a 420 MW triple-pressure reheat CCGT and evaluate its technical and economic performance under full and part load conditions. We evaluate the technical performance of our CCGT model by comparison to an equivalent model implemented in Thermoflow THERMOFLEX and observe agreement of power output and efficiency to within 4.1% and the temperature profile within the HRSG within 2.9%. We further integrate the CCGT with a dynamic model of an amine based CCS process, and observe a reduction in the base plant efficiency from 51.84% at full-load and 50.23% at 60% load by 8.64% points at full-load and 7.93% points at 60% load. A core conclusion of this paper is that CCGT power plants equipped with post-combustion CCS technologies are well suited to dynamic operation, as might be required in an energy system characterised by high penetrations of intermittent renewable power generation.